La tierra moler o "diatomita" como sistema de remoción de sustancias químicas en el laboratorio. - Alfaro Vargas, Ariel (Universidad de Costa Rica, 2009)
Experiments were carried out, to determine the capability of diatomite for the disposal of laboratory residues. Experimentation with different organic solvents (ethyl ether, acetone, ethyl acetate, hexane and ethanol) verified that there is no solvent absorption in the mineral material. Experiments were also carried out with heavy metal cations, in order to quantify their absorption or adsorption in the porous mineral. Ion sequestration was determined and the following order resulted: Cr3+ > Pb2+ > Ag+ > Ni2+ > Zn2+ > Cr2O7 2-. The effect of pH was also studied with nickel, 99,5% removal was observed at pH 7, SO4 2- was 98% removed, followed by Cl - and NO3-. The ideal cation concentration was 4 ppm with a removal efficiency of 99,5%. It is possible to conclude that the absorption material can be used as effusion containment system, rather than a material to eliminate laboratory residues.